Strisce digitali. Forme narrative e trasformazioni culturali nel fumetto contemporaneo - Lorenzo Di Paola (Funes)
Since its appearance, in US newspapers to today, comics have travelled through eras, societies and formats, constantly adapting to changes in the media landscape and managing to embody in their narrative devices the great social traumas derived from the innumerable turning points that humanity is forced to get through. The digital revolution could not fail to involve this medium, which has always been linked to paper technologies, changing narrative strategies, production, consumption, public relations and the very identity of comics. In this paper, through To be Continued analysis - award-winning web comic by Lorenzo Ghetti - we want to try to understand how anthropological/cultural mutations, myths and social traumas find a space of representation in the new semiotic and spatial structures of digital comics, in which different and more complex gaze dynamics they help rewrite narrative techniques and practices. The encounter/clash between comics and digital can allow us to reflect on social, political, cultural and media transformations, on the production and consumption strategies that currently circulate on the web and on the main consequences that reading and digital writing have on the human thought.